(untitled) (Annals of Library and Information Studies, 2025)
The study examined how information literacy (IL) initiatives are managed and implemented within the libraries of select Institutes of National Importance from the perspective of librarians. The research employed a survey method using a Google Form questionnaire and a non-probability sampling technique to gather responses, with 38 librarians participating. The findings indicate that library orientation sessions are one of the most impactful methods for providing services in selected libraries for delivering information literacy to users. Libraries face challenges in implementing or organizing information literacy due to a lack of active participation, limited staff expertise, resistance to change, or adoption of new methods. Researchers have proposed that faculty should be instrumental in motivating and mobilizing students to undertake information literacy programs that their libraries offer. The study reveals that no credit score system in institutions is awarded for participating in IL programs offered by their libraries. It is imperative that this model of add-on (2/3) credit scores in the academic curriculum may prove to be an important component in the academic learning outcomes of the students. The study suggests and concludes that there is an urgent need to work systematically on the policies and standards that offer guidelines and strategies for revamping information literacy by integrating the information literacy concept into the curriculum of HEI’s academic program for all categories of students (Undergraduate, Post Graduate, Professional Courses like B.Tech, M.Tech, M.BA, etc.) as a mandatory course.